2012
DOI: 10.1021/pr300430u
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacometabonomic Characterization of Xenobiotic and Endogenous Metabolic Phenotypes That Account for Inter-individual Variation in Isoniazid-Induced Toxicological Response

Abstract: An NMR-based pharmacometabonomic approach was applied to investigate inter-animal variation in response to isoniazid (INH; 200 and 400 mg/kg) in male Sprague-Dawley rats, alongside complementary clinical chemistry and histopathological analysis. Marked inter-animal variability in central nervous system (CNS) toxicity was identified following administration of a high dose of INH, which enabled characterization of CNS responders and CNS non-responders. High-resolution post-dose urinary ¹H NMR spectra were modele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 55 publications
0
24
1
Order By: Relevance
“…1824 For example, recent metabolomics studies have provided insight regarding potential biomarkers for graft versus host disease (GVHD) in allogeneic HCT recipients. 25, 26 More specifically, Clayton, et al, introduced the concept of personalized drug treatment using pre-dose metabolite profiling to predict drug response in individual subjects, which the authors termed, “pharmacometabonomics”.…”
Section: Introductionmentioning
confidence: 99%
“…1824 For example, recent metabolomics studies have provided insight regarding potential biomarkers for graft versus host disease (GVHD) in allogeneic HCT recipients. 25, 26 More specifically, Clayton, et al, introduced the concept of personalized drug treatment using pre-dose metabolite profiling to predict drug response in individual subjects, which the authors termed, “pharmacometabonomics”.…”
Section: Introductionmentioning
confidence: 99%
“…Cunningham et al [85] also used an NMR-based approach to predict the central nervous system (CNS) toxicity of the anti-tubercular drug isoniazid in rats when dosed at 200 and 400 mg/kg. Isoniazid has a complex metabolic fate, including conjugating with pyruvate and pyridoxal to form pyruvate isonicotinylhydrazone and isoniazidyl-pyridoxal metabolites respectively.…”
Section: Nmr-based Pre-clinical Pharmacometabonomics Studiesmentioning
confidence: 99%
“…It was hoped that this pre-clinical study, the first to identify multiple isoniazid urinary metabolites, would have the ability to translate its finding to the human clinical setting. [85] Coen et al [86] used an NMR-based approach to investigate variability in the response of rats to the toxicity of galactosamine, a drug whose variable responses in rats triggered the design of the original pharmacometabonomics experiment. [46] Male Sprague-Dawley rats were dosed intraperitoneally with 415 mg/kg galactosamine and classified as responders or non-responders based on clinical pathology.…”
Section: Nmr-based Pre-clinical Pharmacometabonomics Studiesmentioning
confidence: 99%
“…Similarly, Cunningham et al found a metabolite signature response to isoniazid in urine that could be used to determine an individual's risk for certain ADRs. 81 However, a drug's effect on urine metabolites can be mitigated or exacerbated by other factors, such as diet, culture, and ethnicity. 82 In summary, understanding a patient's precise microbiome, metabolome, and diet can help researchers understand the underlying cause of an ADR in a population subset.…”
Section: Lifestyle-induced Adr Susceptibilitymentioning
confidence: 99%